L-plastin is involved in NKG2D recruitment into lipid rafts and NKG2D-mediated NK cell migration - Serrano-Pertierra, Esther; Cernuda-Morollón, Eva; Brdička, Tomáš; Hoøejši, Václav; López-Larrea, Carlos (Journal of leukocyte biology, 2014)
Membrane rafts are microdomains of the plasma membrane that have multiple biological functions. The involvement of these structures in the biology of T cells, namely in signal transduction by the TCR, has been widely studied. However, the role of membrane rafts in immunoreceptor signaling in NK cells is less well known. We studied the distribution of the activating NKG2D receptor in lipid rafts by isolating DRMs in a sucrose density gradient or by raft fractionation by β-OG-selective solubility in the NKL cell line. We found that the NKG2D-DAP10 complex and pVav are recruited into rafts upon receptor stimulation. Qualitative proteomic analysis of these fractions showed that the actin cytoskeleton is involved in this process. In particular, we found that the actin-bundling protein L-plastin plays an important role in the clustering of NKG2D into lipid rafts. Moreover, coengagement of the inhibitory receptor NKG2A partially disrupted NKG2D recruitment into rafts. Furthermore, we demonstrated that L-plastin participates in NKG2D-mediated inhibition of NK cell chemotaxis.
Keywords: Detergents; mikrofilamenta; NK Cell Lectin-Like Receptor Subfamily C; proteom; membrane rafts; buňky NK; mikrofilamentové proteiny; Centrifugation, Density Gradient; NK Cell Lectin-Like Receptor Subfamily K; Proteome; lidé; Receptors, Immunologic; lektinové receptory NK-buněk - podrodina C; membránové mikrodomény; malá interferující RNA; signální transdukce; Chemotaxis, Leukocyte; kultivované buňky; Signal Transduction; receptory imunologické; Humans; Cells, Cultured; Killer Cells, Natural; RNA, Small Interfering; Multiprotein Complexes; lektinové receptory NK-buněk - podrodina K; RNA Interference; centrifugace - gradient hustoty; chemotaxis; chemotaxe leukocytů; Membrane Microdomains; RNA interference; buněčná membrána; Microfilament Proteins; detergenty; Actin Cytoskeleton; Cell Membrane; multiproteinové komplexy